Supply chain and agroexport in an agricultural company - Rivas Mio, Miriam Estefany; Cosio Borda, Ricardo Fernando; Robladillo Bravo, Liz Maribel; Quispe-Farfán, Percy Hugo; Noriega-Monar, Gloria; Cordova Godos, Rosita Elena (LACCEI, 2025)
The main objective of this research is to identify the relationship between the supply chain and agro-export in an agricultural company. The methodology used is applied, with a quantitative approach, using the hypothetical-deductive method and a non-experimental cross-sectional design. The results indicate that optimized management at each stage of the supply chain contributes significantly to export success. A moderate positive relationship was found between procurement, production, distribution and agroexport, with a particularly strong impact on the distribution phase. This finding suggests that improving logistics, reducing delivery times and optimizing the distribution chain increases a company’s competitiveness in international markets. The research concludes that an efficient supply chain is key to sustainability and growth in the agroexport sector, recommending that the company focus on implementing logistics management technologies and training its personnel to improve processes and respond to the demands of the global market.